1970
DOI: 10.6028/nbs.sp.317v1
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental aspects of dislocation theory

Abstract: £^t j 3t j These Proceedings contain research papers, discussions thereon, and panel discussions for the conference on "Fundamental Aspects of Dislocation Theory," held under the auspices of the Institute for Materials Research, April 21-25, 1969, at the laboratories of the National Bureau of Standards, Gaithersburg, Maryland. Approximately 75 contributed papers and two panel discussions are included. Topics covered are Dis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(45 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Finally, we need to comment on earlier, similar works that have analyzed the stability of dislocations at high velocities: Our result disagrees with the earlier assessment of ref. [45] (see also [46]), whose author found that screw dislocations become unstable at high velocities whereas edge dislocations remain stable. On the other hand, our results are in perfect agreement with ref.…”
Section: Line Tension and Stabilitymentioning
confidence: 99%
“…Finally, we need to comment on earlier, similar works that have analyzed the stability of dislocations at high velocities: Our result disagrees with the earlier assessment of ref. [45] (see also [46]), whose author found that screw dislocations become unstable at high velocities whereas edge dislocations remain stable. On the other hand, our results are in perfect agreement with ref.…”
Section: Line Tension and Stabilitymentioning
confidence: 99%
“…The total stress field and the total distortion field can be decoupled according to [16] a (lid = Oij q-Old a B, = ~, + fi;;;…”
Section: 2)mentioning
confidence: 99%
“…The dislocations must be extended into partials, more widely separated in this met~ than in Cu, and thus their climb is difficult, as postulated by Seeger [7,8]. [29] 14.17 -+ 2.13 Englert, Tompa and 70 BuUough (1970) [30] Stobb and Sworn (1971) [31] 41 These conclusions lead to two hypotheses about the mechanism of polygonization of the metals in study:…”
Section: Influence Of Impurities In Polygonization Of F C C Metals Of...mentioning
confidence: 91%